Oputa on fair hearing : a selection of his Supreme Court judgments - Nkire, Theo (Abuja Nigeria : Niger Press, 2009)
A survey of some of the judgements written by the revered Jurist, Justice Oputa, on the subject of fair hearing during the period. It gives insight into the mind of Oputa and exposes one to the some of the finest pieces of legal writing in jurisprudence.
oif 11/07/14
Loan
Keywords: Oputa, Chikwudifu Akunne; Justice, Administration of -- Nigeria. Jurisprudence -- Nigeria. Law -- Nigeria. Nigeria -- Supreme Court. &#x000A